Differences in quantification of DNA double-strand breaks assessed by 53BP1/γH2AX focus formation assays and the comet assay in mammalian cells treated with irradiation and N-acetyl-L-cysteine. (21st June 2016) - Kurashige, Tomomi; Shimamura, Mika; Nagayama, Yuji
Abstract: The biological effect of ionizing radiation (IR) on genomic DNA is thought to be either direct or indirect; the latter is mediated by IR induction of free radicals and reactive oxygen species (ROS). This study was designed to evaluate the effect of N-acetyl-L-cysteine (NAC), a well-known ROS-scavenging antioxidant, on IR induction of genotoxicity, cytotoxicity and ROS production in mammalian cells, and aimed to clarify the conflicting data in previous publications. Although we clearly demonstrate the beneficial effect of NAC on IR-induced genotoxicity and cytotoxicity (determined using the micronucleus assay and cell viability/clonogenic assays), the data on NAC's effect on DNA double-strand break (DSB) formation were inconsistent in different assays. Specifically, mitigation of IR-induced DSBs by NAC was readily detected by the neutral comet assay, but not by the γH2AX or 53BP1 focus assays. NAC is a glutathione precursor and exerts its effect after conversion to glutathione, and presumably it has its own biological activity. Assuming that the focus assay reflects the biological responses to DSBs (detection and repair), while the comet assay reflects the physical status of genomic DNA, our results indicate that the comet assay could readily detect the antioxidant effect of NAC on DSB formation. However, NAC's biological effect might affect the detection of DSB repair by the focus assays. Our data illustrate that multiple parameters should be carefully used to analyze DNA damage when studying potential candidates for radioprotective compounds.